A chemical state resolved x-ray photoelectron diffraction study: Initial stages in diamondlike carbon film deposition - Agostino, R. G.; Küttel, O. M.; Aebi, Philipp; Fasel, R.; Osterwalder, J.; Schlapbach, Louis (My University, 1996)
The structural sensitivity of x-ray photoelectron diffraction is greatly enhanced by the acquisition of a full hemispherical diffraction pattern of chemically shifted core levels. Complex systems can be studied resolving the local order per element and per chemical environment. This technique is applied to study the earliest stages of hydrogenated diamondlike carbon film deposition on Si(001). Effects of the sample temperature and ion dose on the structure of deposited layers are discussed.